The Practice of Anal Dilations following Anorectal Reconstruction in Patients with Anorectal Malformations: An International Survey - Brisighelli, Giulia; Morandi, Anna; Di Cesare, Antonio; Leva, Ernesto (European Journal of Pediatric Surgery, 2016)
Purpose The objective of this study was to investigate the current practices of anal dilations after anorectal reconstruction for anorectal malformations (ARMs) in different centers.Materials and Methods An online survey, consisting of 27 questions about the practice of anal dilations, was launched in March 2015 among 54 pediatric surgeons with expertise in colorectal surgery. The survey was divided into three sections. The first section included questions regarding the country of origin, the role in the department, the average number of ARM cases treated per year, and the surgical approach used to repair ARMs. The second section was accessible only for surgeons who perform anal dilations and enquired about their modality of performing anal dilations—their attitude toward complications such as rectal prolapse, bleeding, or perineal dehiscence occurring during dilations—and about the incidence of rectal prolapse and/or anal stenosis, which required surgical repair, in their series of patients with ARMs. The third section was accessible only for surgeons who do not perform anal dilations and enquired the incidence of rectal prolapse and/or anal stenosis that required surgical repair in their series of patients with ARMs.Results A total of 36 pediatric surgeons from 20 countries completed the survey. All participants performed anal dilations. Twenty-five (70%) surgeons performed the first dilation 14 days after anorectal reconstruction; 30 (83%) surgeons performed it in the outpatient clinic; 34 (94%) surgeons used metal dilators and 30 (83%) surgeons lubricated the dilator with an anesthetic/steroid-free ointment; 21 (59%) surgeons tailored the first dilator size to the specific anatomical features of each patient; 27 (75%) surgeons used 1-mm-diameter increments in the dilator size and 22 (61%) surgeons increased the size weekly; 16 (45%) surgeons followed up with the patients weekly until the proper dilator size was reached. This was determined according to Peña's protocol by 25 (70%) surgeons: 23(64%) surgeons initially performed dilations twice daily; 24(66%) surgeons tapered the frequency of dilations once the desired caliber was reached. No general agreement exists in the management of complications such as rectal prolapse, bleeding, or perineal dehiscence occurring during dilations. Incidence of rectal prolapse and anal stenosis was reported less than 5%, respectively, by 25(70%) and 29(81%) respondents.Conclusion Anal dilations for ARM are performed worldwide according to different modalities. Prospective and randomized clinical trials could be useful to establish a standardized protocol.
Keywords: anorectal malformations; anal dilations; survey; anorectal reconstruction